Perencanaan Kebutuhan Baku dengan ARIMA dan EOQ - Mawadati, Argaditia; Wibowo, Agus Hindarto; Prima, Melanisa Ade (Jurnal Teknologi, Fakultas Teknik, Universitas AKPRIND Indonesia, 2023)
A production plan will run well if it is supported by an adequate supply of raw materials. Raw material procurement at PT Pura Barutama is done by asking suppliers to send raw materials to the warehouse every day with an uncertain amount. As a result, there is a buildup of raw materials in the warehouse. This accumulation of raw materials poses a risk of loss because the raw materials used are materials that are prone to damage, if this happens, the company will experience a loss in purchasing costs. The purpose of this study is to determine the amount of raw material orders using the ARIMA method for forecasting raw material requirements and Economic Quantity Order (EOQ) to determine the point of reordering raw materials. The results showed that the use of EOQ can save the total cost of raw material inventory up to Rp 53,549,222. It is concluded that the optimal amount of raw material ordering is 19591.8 Kg / order, ordering is done 10 times a year and the company's raw material reorder point is when the amount of raw material is 668.71 Kg, thus the company does not experience excess raw materials.